Having Conversations about Organ Donation - Sadler, Blair L. (The Hastings Center report, 2015)
While 90 percent of participants in a 2005 Gallup poll indicated that they would donate an organ if asked, only 40 percent of Americans have registered to do so, according to 2012 data from Donate Life America; likely even fewer have shared their donation wishes with loved ones. Undoubtedly, the single biggest reason for the discrepancy between the number of potential transplants and the number actually performed is our failure to talk with loved ones about our wishes regarding organ donation. Although many resources already exist to hold these conversations, we can do more, and the emergence of social media provides an intriguing new opportunity. Two years ago, Organize.org set out to create the first nationwide organ donation registry in the United States.